Typifications and a new name in Filago (Gnaphalieae, Asteraceae) - Andrés-Sánchez, Santiago; Martínez-Ortega, M. Montserrat; Rico, Enrique (Phytotaxa, 2016)
This paper is focused on the typification of 36 names provided for Filago species in order to fix their correct usage. Eight of them are accepted names, basionyms or replaced synonyms of accepted names at the specific rank, i.e. F. abyssinica, F. argentea, F. carpetana, F. contracta, F. eriocephala, F. lutescens, F. lusitanica and F. tyrrhenica. Many others have been extensively used in the taxonomic literature related to the genus (e.g., F. apiculata, F. canescens or F. spathulata). Thirty four lectotypes, three epitypes and one neotype have been selected according to the International Code of Nomenclature for Algae, Fungi, and Plants. Further specimens and/or materials relevant to typification are indicated, together with protologue citations. Finally, Filago albicans is proposed as a replacement name for the illegitimate combination F. atlantica.